Segmental hemangioma with soft tissue hypertrophy. - Mazzotta, F. (European Journal of Pediatric Dermatology, 2018)
In the past (1) we showed that the segmental precursors of the limbs can be associated with ischemic arteriopathic lesions to cause mold ulcerative lesions and we found that these findings supported the role of tissue hypoxia in the pathogenesis of hemangioma. It is possible that the hypothermia of the segmental hemangioma of the current case is a confirmation of vascular disorders associated with hemangioma, although not demonstrable with the actually available diagnostic methods. Our data were confirmed by a recent report (2) on segmental precursors of the limbs that are also called minimal or arrested growth infantile hemangiomas. The report, while emphasizing the hypertrophy of the soft tissues, the pastiness of the skin and the presence of very evident superficial veins, highlighted in some cases ulcerative lesions and hypothermia of the affected limb.